PELAKSANAAN PENILAIAN PRESTASI KERJA PEGAWAI BERDASARKAN PP NO. 46 TAHUN 2011 DINAS KOPERASI, USAHA MIKRO SEMARANG - Arin Nisrina; Herbasuki Nurcahyanto; Rihandoyo Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Evaluation of the employees performance are important factor as a measure that can be used to reform and improve performance employees. Assessment work performance use DP-3 in the neighborhood civil servants are considered no effective because cannot be used for measuring how much productivity and contribution given civil servants over organisation. Assessment DP-3 are more oriented towards on judgment personality and behavior. The assessment system of repair work performance employees combining of elements target work civil servants and behavior work set in government regulation number 46/2011. One government agencies apply the assessment system of work performance use element target work civil servants and behavior work were dept. of cooperatives or for micro and the city of Semarang. The results of the study show the work performance in the office for cooperatives and micro business have led to theories management, but there are still requirement in assessment work performance that have not been. In terms of input on who provide an assessment have not been in accordance with government regulation number 46/2011. In terms of the process is good only not optimal because employees still needs to be given trainings periodically. In terms of output assessment work performance employees referring to government regulation number 46/2011 able to increase work performance employees, encourage motivation, and increase discipline. Keywords: